Chemical constituents isolated from Antarctic marine-derived Aspergillus sp SF-5976 and their anti-inflammatory effects in LPS-stimulated RAW 264.7 and BV2 cells - Kwon, Jaeyoung; Lee, Hyaemin; Ko, Wonmin; Kim, Dong-Cheol; Kim, Kwan-Woo; Kwon, Hak Cheol; Guo, Yuanqiang; Sohn, Jae Hak; Yim, Joung Han; Kim, Youn-Chul; Oh, Hyuncheol; Lee, Dongho (Pergamon Press Ltd., 2017)
Three new benzaldehydes (1-3) and two new dioxopiperazine alkaloids (4 and 5), along with 23 known constituents, were isolated from Antarctic marine-derived Aspergillus sp. SF-5976. Their structures were determined by spectroscopic and chemical methods. Among them, 20 compounds showed inhibitory effects toward lipopolysaccharide (LPS)-induced, nitric oxide (NO) production in RAW 264.7 macrophages with IC50 values of 7.3-77.4 mu M, while 22 compounds did in BV2 microglia with those of 4.6-72.3 mu M. Furthermore, the effects of the newly isolated compounds on LPS-stimulated inducible NO synthase (iNOS) expression were investigated, and 1-3, and 5 inhibited iNOS in RAW 264.7 cells, while 1-5 did in BV2 cells. Also, 1-3 and 5 inhibited LPS-induced prostaglandin E-2 production with IC50 values of 9.1 -66.8 mu M in RAW 264.7 macrophages by suppressing cyclooxygenase-2 (COX-2), while in BV2 microglia, 1-5 showed activities with those of 2.8-49.4 mu M. (C) 2017 Elsevier Ltd. All rights reserved.